Croatia and Euroepan Integrations in the Early Middle Ages - Budak, Neven (Array, 2008)
During the early Middle Ages (9th - 11th c.) Croatia was positioned between the Byzantine and the Carolingian or Ottonian Empire. It underwent integration processes regarding political, religious, and cultural aspects. The paper briefly discusses all of these processes and their consequences for the development of medieval Croatia.